The role of financial inclusion and ICTs in shaping inclusive growth: A bibliometric analysis of past, present, and future trends - Amaluddin, Amaluddin; Leasiwal, Teddy Christianto; Manuhutu, Yerimias (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
This study conducts a comprehensive bibliometric analysis to map and review the scientific literature on the role of financial inclusion (FI) and information and communication technologies (ICTs) in fostering inclusive growth, using the Scopus database. Although previous studies have examined FI, ICTs, and inclusive growth separately, few have systematically integrated their intellectual structures into a unified framework. The bibliometric analysis includes co-citation, bibliographic coupling, and co-word analyses, supported by VOSviewer software. The findings indicate that digital finance plays a significant role in driving financial inclusion and inclusive growth. Current research shows that financial inclusion reduces poverty and income inequality, while ICTs promote economic growth and innovation in fintech and digital financial systems. Emerging themes, including digital financial inclusion, fintech, microfinance, innovation, and sustainability, represent important research trends and future directions. Overall, the integrated findings demonstrate the growing role of digitally enabled financial systems in supporting inclusive economic development.